Parasitoide Opius sp. (Hymenoptera: Braconidae) no manejo integrado da mosca minadora na cultura do meloeiro - Nogueira, Carlos Henrique Feitosa (2012)
The states of Rio Grande do Norte and Ceará are the main producers of melons from Brazil. They account for about 90% of national production, which makes the growth of melon Cucumis melo L. one of the main segments of agribusiness in these states. Despite the high technology used for the cultivation of this vegetable crop, this crop has suffered serious damage due to attack of the leafminer Liriomyza sativae (Diptera: Agromyzidae). The control method used by manufacturers to control this pest is basically the use of chemical insecticide, however, the exclusive use of this method has not been satisfactory for suppressing the population of insect biological control and using the parasitoid Opius sp. (Hymenoptera: Braconidae) has been shown to be a promising technique for controlling this pest in melon. Thus, this study aimed to estimate the number of parasitoids to be released in the field and evaluate the effect of insecticides on it, under field conditions. Among the ratios evaluated the proportion of 1:10 (one every ten parasitoid larvae) was the one with the highest rate of emergence of parasitoid 33.13%. Among the insecticides evaluated in the first trial, was observed at all doses of Neem Oil that the rate of emergence of the parasitoid Opius sp. was not different from control, whereas treatment with the lowest Abamectin rate was verified emergency 2.24%, differing from all other treatments. In the second experiment, we observed that treatment with the active Deltamethrin was the highest rate of reduction in population of the parasitoid Opius sp. (71.4%), followed by Abamectin and Cartap Hydrochloride (50.5 and 14.4% respectively)